Borderline ovarian clear cell tumor arising from endometriosis during long-term dienogest therapy: a case report - Shang, Kaiyue; Xing, Hongxin; Zhang, Suzhen; Zhang, Yazhou; Zhang, Hui (Frontiers in Oncology, 2025)
Endometriomas, commonly known as ovarian chocolate cysts, are a prevalent condition in women of reproductive age. They are cysts formed by the ectopic growth of endometrial tissue within the ovary, often leading to dysmenorrhea and infertility. Dienogest is a first-line medication for the long-term management of endometriomas, control of associated pain, and prevention of postoperative recurrence. A 34-year-old woman presented to our hospital with dysmenorrhea and was diagnosed with an endometrioma. She subsequently commenced dienogest treatment for a total duration of thirty-two months. During this period, the cyst gradually decreased in size and eventually became undetectable. However, a follow-up ultrasound indicated the recurrence of the endometrioma after twenty-seven months. Five months later, a subsequent ultrasound revealed papillary growth with internal blood flow within the ovarian endometrioma. The patient underwent immediate surgical intervention. The postoperative pathology indicated a borderline clear cell tumor. Consequently, the patient promptly underwent comprehensive staging surgery, with the final pathology confirming no residual tumor. This case demonstrates that despite long-term and effective dienogest treatment, endometriomas retain the potential for malignant transformation. Therefore, regular monitoring during treatment and prompt intervention upon suspicion of malignancy are indispensable.